Hubungan lama paparan debu kayu dan kedisiplinan pemakaian masker dengan penurunan kapasitas fungsi paru pada pekerja mebel ud. mita furniture kalinyamatan jepara - Miftakhurizka, Muhammad, Tarwaka, PGDip Sc, M.Erg, Tri Puji Kurniawan, SKM, M. Kes (2014)
Wood processing industry is one industry that is growing very rapidly. One of the negative impacts of the wood processing industry is the emergence of air pollution by dust or result. Wood furniture industry workers have a very big risk for the accumulation of dust in the respiratory tract that may affect human health, especially lung function impairment. The purpose of this study was to determine the relationship of long exposure to wood dust and discipline the use of a mask with a decrease in furniture workers UD. Mita Kalinyamatan Furniture Jepara. This study is an observational analytic cross-sectional approach. Study population was all male workers in the production of as many as 22 workers. The research sample using total sampling technique. Statistical tests using Pearson Product Moment Correlation test with the results obtained by analysis of the value of p = 0.02 <0.05 and r = -0.493 (quite strong). Additionally obtained p value = 0.001 <0.05 and r = -0.646 correlation value (strong) which means there is the use of a mask of discipline relationship with lung function decline in the capacity of workers.